A hibridação cultural em Iracema: representação Alencariana da formação do povo brasileiro - Pereira, Priscila Magalhães (2022)
With the study of the literary work Iracema, of Ceará-born José de Alencar (1889), we realize that this writer approaches the formation of the Brazilian people as constituted of a hybrid way from residues of European and Indigenous cultures. In that, we aim to understand how residues of different cultures were combined by Alencar to composse something new, crystalized in the work in question, and in what way this book can be read as a representation of the hybridization that occurred in the formation of the Brazilian people. To achieve that, we utilized the operational concepts of Theory of Residuality, systematized by Roberto Pontes, especially of cultural hybridization. Thus, it was necessary to present a brief setting of the hystorical past of Brazil, from the sixteenth century until the first half of the nineteenth century; to analyze Iracema from the residual perspective of a narrative of origin; to identify the residues of different cultures present in the work; that contributed to the hybrid representation of the Brazilian people and to describe in what way the cultural representation happens in the studied representation. To reach the proposed goals, we have organized the present work in three parts. On the first part, we have traced a brief panorama of the hystorical Brazilian past; from the arrival of the Portuguese to the first half of the nineteenth century, when the romantic writers, among them José de Alencar, undertook the search for the national identity as a literary project. On the second part, we have analyzed the book from the residual perspective of a narrative of origin, talking more in depth about the Theory of Residuality and the operational concepts that compose it. On the third part, we work in a detailed way with the operational concept of cultural hybridization, from the perspective of the Theory of Literary and Cultural Residuality, from the studies of its systematizer, identifying, in the literary work, the residues of the referred cultures in the formation of the Brazilian people represented in it. It is a comparative analysis between literary, hystorical, sociological and anthropological texts, with the use of a qualitative approach. Among the theoreticians that contributed to the present research, we can name: Vainfas (1995 and 2010), Anderson (2008), Cândido (1959, 2000 and 2002), Cascudo (2012), Burke (2003), Canclini (1998) and Pontes (2017, 2020a and 2020b). We have considered all of the presented conceptions to be essential to the understanding that, in the work Iracema, the formation of the Brazilian people is constituted in a hybrid way, through the residues of Indigenous and European cultures, that find themselves hybridized in the construction of the Alencarian characters Iracema, Martim, Poti and Moacir, the Brazilian formed in a hybrid way.